Awareness, attitude, and acceptance of newborn screening for sickle cell disease among health workers and caregivers at primary healthcare centers in Gwagwalada Area Council, Federal Capital Territory, Abuja, Nigeria - Hezekiah A, Isa; Oparaugo, Chisomaga Ifeanyi; Ajetomobi, Grace Doyin; Fasina, Ayomide Esther; Chianumba, Reuben Ikechukwu; Nnodu, Obiageli Eunice (Frontiers in Public Health, 2025)
IntroductionNewborn Screening (NBS) is a public health program designed to identify and provide early interventions for infants with genetic disorders such as Sickle Cell Disease (SCD). Lack of awareness and unwillingness to participate in the NBS by caregivers and some healthcare workers are major contributing factors impeding NBS for SCD.ObjectiveTo evaluate the level of awareness and acceptance of NBS for SCD and the determinant factors influencing caregivers in Gwagwalada Area Council of the Federal Capital Territory, Abuja, Nigeria.MethodsThe study employed a descriptive, quantitative design using questionnaires administered to healthcare workers and caregivers at immunization and antenatal clinics of 10 selected Primary Healthcare Centers (PHC) in Gwagwalada Area Council of the Federal Capital Territory, Abuja, Nigeria.ResultA total of 357 participants, comprising 301 caregivers and 56 health care workers responded to the questionnaires. Among the caregivers, 171 (57.2%) were not aware of NBS for SCD. Two hundred and ninety (97%) expressed willingness to participate in the NBS. However, 32 (10.6%) indicated reluctance to accept positive results of SCD. The majority, 175 (59.1%) of the caregivers strongly agreed that NBS for SCD helps in the early detection and management of SCD, while 7 (2.4%) disagreed. Notably 272 (90.4%) of the caregivers had secondary and tertiary education. Among the healthcare workers, 39 (73.6%) were aware of NBS for SCD and 30 (73.2%) have recommended it to caregivers.ConclusionThis study revealed a low level of awareness of NBS for SCD among caregivers. However, there was a high level of acceptance among them. The level of awareness is high among healthcare workers. Education emerged as the major factor determining the knowledge and attitude of caregivers toward NBS for SCD.